More than just a carding system: Labour implications of the EU's illegal, unreported and unregulated (IUU) fishing policy in Thailand. (May 2021) - Kadfak, Alin; Linke, Sebastian
Abstract: Globally, the EU plays a leading role in combating illegal, unreported and unregulated (IUU) fishing activities. Specifically, the EU exercises normative power to influence regulatory strategies and governing frameworks in third countries. In 2015, the EU issued Thailand a yellow card, indicating that economic sanctions would be implemented unless IUU fishing practices were eliminated. Concurrently, revelations about 'modern slavery' in Thailand's fishing industry had received international attention, through media and NGOs, exposing slavery-like practices among migrant fishworkers. Conventionally, the EU's IUU policy addresses only issues of catch and environmental sustainability. This paper explores how an initial bilateral dialogue was bifurcated into two dialogues: a Fishery Dialogue and a Labour Dialogue. Drawing on semi-structured interviews with involved actors, expert opinions, field-visits and secondary documents, we ask: How were labour issues integrated into the bilateral dialogue, and what consequences emerged from the IUU policy for Thai fisheries management? Tracing the bilateral dialogue between EU and Thai governments, we argue that Thailand's fisheries reform was a result of both fisheries' sustainability concerns and the kind of labour rights valued by the EU. Our Normative Power Europe approach shows how norms of labour rights shaped the reform through policies and implementation. We maintain that this unique case-study reveals how the EU incorporates a broad-based normative approach that goes beyond catch sustainability. Highlights: The paper explores the integration of labour rights in the EU IUU dialogue. The paper uses a Normative Power Europe approach in global fisheries context. The paper brings together IUU practices and the violation of labour rights. The paper explores social criteria integration in EU's external fisheries policies.